Screening Earth Analog Exoplanets on the Basis of a Predicted Nitrogen over Phosphorus Ratio - Hervé Toulhoat (The Astrophysical Journal, 2023)
Since the first discovery in 1995, data for over 5300 exoplanets have been documented in the NASA archive, revealing a vast diversity. Identifying life-enabling analogs of the Earth among this rapidly expanding catalog is of major interest. The stability of liquid water at the planetary surface defining the concept of the habitable zone (HZ) around the host star, may be necessary for the emergence of life as we know it but not sufficient. The practically constant atomic ratio nitrogen:phosphorous = 16:1 in oceanic surface layers of our planet Earth was discovered by Redfield in 1934. It corresponds to phytoplanktonic biomass in suspension and appears optimal to fertilize phytoplankton development and therefore the food pyramid of marine life. Loladze and Elser have shown that it corresponds to a homeostatic protein:RNA ratio and is therefore “rooted in the stoichiometry of the foundational structures of life.” I show that according to the recent theory of the chemical differentiation of planets, this optimal ratio is also an intrinsic chemical property of our planet Earth uniquely determined in the solar system by its average orbital radius. On that basis, I propose a criterion of fertility within the HZ of a stellar system, which when applied to screen the public database allows us to sort out an extended list of up to 74 Earth analogs. The latter and its future extensions could provide priority targets for focused detection techniques.